1994
DOI: 10.1103/physrevb.50.9595
|View full text |Cite
|
Sign up to set email alerts
|

Crystallography and magnetism of the heavy-fermion compound YbBiPt

Abstract: The super-heavy-fermion compound YbBiPt has the largest known linear specific-heat coe5cient y =8 Jmol ' K, and the source of this enormous "electronic" specific heat is of great current interest.Here we describe neutron-diffraction studies that indicate its previously reported crystallographic structure to be incorrect. %'e find that the Pt atom is on the unique site and can be thought of as an interstitial in a fictitious rock-salt structure YbBi, which can in turn be thought of as an ordered form of element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 12 publications
4
42
0
Order By: Relevance
“…1 are consistent with the lattice being described by a face-centered-cubic space group, which is the symmetry possessed by the lattice at T = 300 K. 9 There are also no indications of the formation of a superstructure, such as the occurrence of additional Bragg peaks upon cooling. In addition to the data shown in Fig.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…1 are consistent with the lattice being described by a face-centered-cubic space group, which is the symmetry possessed by the lattice at T = 300 K. 9 There are also no indications of the formation of a superstructure, such as the occurrence of additional Bragg peaks upon cooling. In addition to the data shown in Fig.…”
Section: Discussionsupporting
confidence: 69%
“…9 The Yb ions are located at the 4d Wyckoff position, forming a face-centered-cubic magnetic sublattice, and the Bi and Pt are located at the 4c and 4a Wyckoff positions, respectively. 9 All three sites possess 43m tetrahedral (i.e. cubic) point-group symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in this structure [3,4] has grown since the discovery by Canfield et al [5,6] that the compound YbBiPt is a cubic heavy-fermion and has the largest known linear specific-heat coefficient, 7 = 8 J/molK 2. This is ten times that of typical heavy-fermions [7] and about a thousand times that of conventional metals.…”
Section: Introductionmentioning
confidence: 99%
“…study [4], we have shown that the Pt ion is on the unique site, in contrast to what had been reported previousl [2]. We have conducted inelastic neutron scattering experiments using the LAM-40 spectrometer [5] at the Japanese National Laboratory for High-Energy Physics (KEK), the QENS spectrometer [6] at Argonne National Laboratory, and the Cold-Neutron Fermi-Chopper Spectrometer [7] at the National Institute of Standards Fig.…”
mentioning
confidence: 99%